A Yersiniabactin-producing Klebsiella aerogenes Strain Causing an Outbreak in an Austrian Neonatal Intensive Care Unit. Issue 7 (7th June 2022) - Baier-Grabner, Sebastian; Equiluz-Bruck, Susanne; Endress, David; Blaschitz, Marion; Schubert, Sören; Indra, Alexander; Fudel, Marta; Frischer, Thomas; Götzinger, Florian
Abstract : Background: Yersiniabactin, a siderophore with a high affinity to iron, has been described as a potential virulence factor in Enterobacteriaceae. Klebsiella aerogenes is a Gram-negative rod known to cause invasive infection in very low birth weight infants but is an unusual pathogen to cause outbreaks in neonatal intensive care units (NICU). Methods: We performed a retrospective analysis of all patients colonized with K. aerogenes in our NICU from September to December 2018. Each infant with an occurrence of K. aerogenes in any microbiological culture was defined as a case. Clinical data were taken from medical charts. K. aerogenes isolates were genotyped using whole-genome sequencing combined with core genome multilocus sequencing type analysis. Yersiniabactin production was evaluated by luciferase assay. Results: In total 16 patients were colonized with K. aerogenes over the 3-month period and 13 patients remained asymptomatic or developed late-onset neonatal sepsis from another pathogen. Three patients developed necrotizing enterocolitis, 2 complicated by sepsis and 1 of them died. All symptomatic patients were premature infants with low birth weight. Genetic sequencing confirmed an outbreak with the same strain, all samples expressed the high-pathogenicity island, necessary for the production of yersiniabactin. Six exemplary cases were proven to produce yersiniabactin in vitro. Conclusion: This is the first report of an outbreak of a yersiniabactin-producing K. aerogenes strain causing invasive infection in preterm infants. We hypothesize that, due to improved iron uptake, this strain was associated with higher virulence than non-yersiniabactin-producing strains. Extended search for virulence factors and genetic sequencing could be pivotal in the management of NICU outbreaks in the future.